Synthesis and investigation on optical and electrochemical properties of 2,4-diaryl-9-chloro-5,6,7,8-tetrahydroacridines - Tka, Najeh; Ayed, Mohamed Adnene Hadj; Braiek, Mourad Ben; Jabli, Mahjoub; Langer, Peter (Beilstein Journal of Organic Chemistry, 2021)
A facile synthesis of 2,4-diaryl-9-chloro-5,6,7,8-tetrahydroacridine derivatives is reported which is based on POCl3-mediated cyclodehydration followed by double Suzuki–Miyaura cross-coupling. The absorption and fluorescence properties of the obtained products were investigated and their HOMO/LUMO energy levels were estimated by cyclic voltammetry measurements. Besides, density functional theory calculations were carried out for further exploration of their electronic properties.
Keywords: catalysis; cross-coupling; cyclization; fluorescence; palladium

(untitled) - Hoang, M. H.; Cho, M. J.; Kim, K. H.; Cho, M. Y.; Joo, J.-s.; Choi, D. H. (Thin Solid Films, 2009)

(untitled) - Payne, A.-J.; McCahill, J. S. J.; Welch, G. C. (Dyes Pigm., 2015)

(untitled) - Pham, H. T.; Lee, D.-S.; Dao, T. D.; Jeong, H.-D. (J. Ind. Eng. Chem. (Amsterdam, Neth.), 2018)

(untitled) - Fujita, T.; Haketa, Y.; Maeda, H.; Yamamoto, T. (Org. Electron., 2017)

(untitled) - Ma, L.; Yu, Y.; Li, L.; Lei, T.; Jiao, B.; Hou, X.; Wu, Z. (Org. Electron., 2018)

(untitled) - Zhao, Q.; Yuan, H.; Xu, X.; Hu, L.; Gong, P.; Yan, Z. (Dyes Pigm., 2019)

(untitled) - Yan, Z.; Wang, C.; Tang, Y.; Zhu, Y.; Cao, Q.; Yang, T.; Hu, L. (Spectrochim. Acta, Part A, 2020)

(untitled) - Reddy, G.; Basak, P.; Jones, L. A.; Della Gaspera, E.; Islavath, N.; Giribabu, L. (Sol. Energy, 2020)

(untitled) - Hong, T. R.; Shin, J.; Um, H. A.; Lee, T. W.; Cho, M. J.; Kim, G. W.; Kwon, J. H.; Choi, D. H. (Dyes Pigm., 2014)

(untitled) - Sun, Z.-Z.; Sun, P.-P.; Feng, S.; Xu, Y.-L.; Liu, J.-F. (Synth. Met., 2019)

(untitled) - Kumar, R.; Kaur, M.; Kumari, M. (Acta Pol. Pharm., 2012)

(untitled) - Schmidt, A.; Liu, M. (Adv. Heterocycl. Chem., 2015)

Biomedical Applications of Acridines; Progress in Drug Research - Ježek, J.; Hlaváček, J.; Šebestík, J. (Syntheses, 2017)

(untitled) - Songbuer; Li, M.; Imerhasan, M. (Chin. J. Org. Chem., 2018)

(untitled) - Demeunynck, M.; Charmantray, F.; Martelli, A. (Curr. Pharm. Des., 2001)

(untitled) - Dopierała, A.; Wrosz, P.; Mazerski, J. (Postepy Hig. Med. Dosw., 2011)

(untitled) - Galdino-Pitta, M. R.; Pitta, M. G. R.; Lima, M. C. A.; Galdino, L. S.; Pitta, I. R. (Mini-Rev. Med. Chem., 2013)

(untitled) - Denny, W. A. (Curr. Med. Chem., 2002)

(untitled) - Valdés, A. F.-C. (Open Med. Chem. J., 2011)

(untitled) - Sondhi, S. M.; Singh, J.; Rani, R.; Gupta, P. P.; Agrawal, S. K.; Saxena, A. K. (Eur. J. Med. Chem., 2010)

(untitled) - Benoit, A. R.; Schiaffo, C.; Salomon, C. E.; Goodell, J. R.; Hiasa, H.; Ferguson, D. M. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Cholewiński, G.; Dzierzbicka, K.; Kołodziejczyk, A. M. (Pharmacol. Rep., 2011)

(untitled) - Singh, H.; Singh, H.; Sharma, S.; Bedi, P. M. S. (Heterocycles, 2015)

(untitled) - Chatterjee, S.; Kumar, G. S. (J. Photochem. Photobiol., B, 2016)

(untitled) - Jiao, J.; Shen, J.; Wang, L.; Xie, Z.; Xia, C.; Xin, X. (Colloids Surf., A, 2018)

(untitled) - Gadah, R. H.; Basaleh, A. S. (Ceram. Int., 2020)

(untitled) - Dai, Q.; Gao, C.; Liu, Y.; Liu, H.; Xiao, B.; Chen, C.; Chen, J.; Yuan, Z.; Jiang, Y. (Tetrahedron, 2018)

(untitled) - Wang, C.; Fu, J.; Yao, K.; Xue, K.; Xu, K.; Pang, X. (Spectrochim. Acta, Part A, 2018)

(untitled) - Bazzicalupi, C.; Bencini, A.; Matera, I.; Puccioni, S.; Valtancoli, B. (Inorg. Chim. Acta, 2012)

(untitled) - Goel, A.; Kumar, V.; Singh, S. P.; Sharma, A.; Prakash, S.; Singh, C.; Anand, R. S. (J. Mater. Chem., 2012)

U.S. Pat. Appl. - Boudreault, P.-L. T.; Alleyne, B.; Xia, C. (Organic electroluminescent materials and devices, 2018)

(untitled) - Wiseman, A.; Sims, L. A.; Snead, R.; Gronert, S.; Maclagan, R. G. A. R.; Meot-Ner (Mautner), M. (J. Phys. Chem. A, 2015)

(untitled) - Gong, X.; Lu, C.-H.; Lee, W.-K.; Li, P.; Huang, Y.-H.; Chen, Z.; Zhan, L.; Wu, C.-C.; Gong, S.; Yang, C. (Chem. Eng. J., 2021)

(untitled) - Chen, J.-X.; Tao, W.-W.; Wang, K.; Zheng, C.-J.; Liu, W.; Li, X.; Ou, X.-M.; Zhang, X.-H. (Org. Electron., 2018)

(untitled) - Stępień, M.; Gońka, E.; Żyła, M.; Sprutta, N. (Chem. Rev., 2017)

(untitled) - Yang, W.; Monteiro, J. H. S. K.; de Bettencourt‐Dias, A.; Catalano, V. J.; Chalifoux, W. A. (Chem. – Eur. J., 2019)

(untitled) - Zhang, J.; Lakowicz, J. R. (J. Phys. Chem. B, 2005)

(untitled) - Sun, W.; Zhou, N.; Xiao, Y.; Wang, S.; Li, X. (Dyes Pigm., 2018)

(untitled) - Kim, M.; Lee, J. Y. (Org. Electron., 2012)

(untitled) - Seo, J.-A.; Jeon, S. K.; Lee, J. Y. (Org. Electron., 2016)

(untitled) - Wang, Z.; Zhang, H.; Wang, Z.; Zhao, B.; Chen, L.; Li, J.; Wang, H.; Hao, Y.; Li, W. (Org. Electron., 2018)

(untitled) - Han, M.; Chen, Y.; Xie, Y.; Zhang, F.; Li, X.; Huang, A.; Fan, Y.; Fan, Y.; Gong, Y.; Peng, Q.; Li, Q.; Ma, D.; et al. (Cell Rep. Phys. Sci., 2020)

(untitled) - Zeng, W.; Lai, H.-Y.; Lee, W.-K.; Jiao, M.; Shiu, Y.-J.; Zhong, C.; Gong, S.; Zhou, T.; Xie, G.; Sarma, M.; Wong, K.-T.; Wu, C.-C.; et al. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Szymański, P.; Markowicz, M.; Mikiciuk-Olasik, E. (Bioorg. Chem., 2011)

(untitled) - Pirrung, M. C.; Chau, J. H.-L.; Chen, J. (Chem. Biol., 1995)

(untitled) - Czarnecka, K.; Chufarova, N.; Halczuk, K.; Maciejewska, K.; Girek, M.; Skibiński, R.; Jończyk, J.; Bajda, M.; Kabziński, J.; Majsterek, I.; Szymański, P. (Eur. J. Med. Chem., 2018)

(untitled) - Bajda, M.; Jończyk, J.; Malawska, B.; Czarnecka, K.; Girek, M.; Olszewska, P.; Sikora, J.; Mikiciuk-Olasik, E.; Skibiński, R.; Gumieniczek, A.; Szymański, P. (Bioorg. Med. Chem., 2015)

(untitled) - Nishibori, M.; Oishi, R.; Itoh, Y.; Saeki, K. (Jpn. J. Pharmacol., 1991)

(untitled) - Liu, Z.; Fang, L.; Zhang, H.; Gou, S.; Chen, L. (Bioorg. Med. Chem., 2017)

(untitled) - Romero, A.; Cacabelos, R.; Oset-Gasque, M. J.; Samadi, A.; Marco-Contelles, J. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Martins, C.; Carreiras, M. C.; León, R.; de los Ríos, C.; Bartolini, M.; Andrisano, V.; Iriepa, I.; Moraleda, I.; Gálvez, E.; García, M.; Egea, J.; Samadi, A.; et al. (Eur. J. Med. Chem., 2011)

(untitled) - Olszewska, P.; Mikiciuk-Olasik, E.; Błaszczak-Świątkiewicz, K.; Szymański, J.; Szymański, P. (Biomed. Pharmacother., 2014)

(untitled) - Wang, S.-L.; Wang, Z.-F.; Qin, Q.-P.; Tan, M.-X.; Luo, D.-M.; Zou, B.-Q.; Liu, Y.-C. (Inorg. Chem. Commun., 2019)

(untitled) - Tripathi, R. P.; Verma, S. S.; Pandey, J.; Agarwal, K. C.; Chaturvedi, V.; Manju, Y. K.; Srivastva, A. K.; Gaikwad, A.; Sinha, S. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Flader, A.; Ohlendorf, L.; Ehlers, P.; Ammon, E.; Villinger, A.; Langer, P. (Adv. Synth. Catal., 2019)

(untitled) - Janke, J.; Villinger, A.; Ehlers, P.; Langer, P. (Synlett, 2019)

(untitled) - Tka, N.; Ayed, M. A. H.; Braiek, M. B.; Jabli, M.; Chaaben, N.; Alimi, K.; Jopp, S.; Langer, P. (Beilstein J. Org. Chem., 2021)

(untitled) - Tka, N.; Jabli, M.; Saleh, T. A.; Salman, G. A. (J. Mol. Liq., 2018)

(untitled) - Jabli, M.; Tka, N.; Ramzi, K.; Saleh, T. A. (J. Mol. Liq., 2018)

(untitled) - Jabli, M.; Tka, N.; Salman, G. A.; Elaissi, A.; Sebeia, N.; Hamdaoui, M. (J. Mol. Liq., 2017)

(untitled) - Modh, R. P.; De Clercq, E.; Pannecouque, C.; Chikhalia, K. H. (J. Enzyme Inhib. Med. Chem., 2014)

(untitled) - Keri, R. S.; Quintanova, C.; Marques, S. M.; Esteves, A. R.; Cardoso, S. M.; Santos, M. A. (Bioorg. Med. Chem., 2013)

(untitled) - Miyaura, N.; Yamada, K.; Suzuki, A. (Tetrahedron Lett., 1979)

(untitled) - Miyaura, N.; Suzuki, A. (J. Chem. Soc., Chem. Commun., 1979)

(untitled) - Qin, Y.; Gu, H.; Liu, S.; Dai, W.; Luo, X. (Synth. Met., 2018)

(untitled) - Melhuish, W. H. (J. Phys. Chem., 1961)

(untitled) - Connelly, N. G.; Geiger, W. E. (Chem. Rev., 1996)

(untitled) - Egbe, D. A. M.; Carbonnier, B.; Paul, E. L.; Mühlbacher, D.; Kietzke, T.; Birckner, E.; Neher, D.; Grummt, U.-W.; Pakula, T. (Macromolecules, 2005)

(untitled) - Zahn, D. R. T.; Gavrila, G. N.; Salvan, G. (Chem. Rev., 2007)

Gaussian 09, Revision B.01 (Gaussian, Inc., 2009)

Chemist’s Guide to Density Functional Theory - Koch, M. W.; Holthausen, C. A. (Wiley-VCH, 2000)